2018
DOI: 10.1051/mbcb/2017028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic stress on periodontal health

Abstract: --Introduction: Periodontal diseases are caused by pathogenic microorganisms that induce increases in of local and systemic proinflammatory cytokines, resulting in periodontal damage. The onset and evolution of periodontal diseases are influenced by many local and systemic risk factors. Educational objective: In this article, we aim to review the results of the research on the impact of chronic stress on the occurrence, development, and response to periodontal disease treatments and on the pathophysiological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
(89 reference statements)
1
23
0
Order By: Relevance
“…The association of stress with periodontal health is difficult to prove as many factors influence the incidence and severity of periodontitis. Negative life events among socially deprived women can be linked with the onset or exacerbation of illness, and the relationship between important negative life events and disease can be mediated by the immune system [ 7 ]. Research has shown that emotional stress can modulate the immune system through the neural and endocrine systems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of stress with periodontal health is difficult to prove as many factors influence the incidence and severity of periodontitis. Negative life events among socially deprived women can be linked with the onset or exacerbation of illness, and the relationship between important negative life events and disease can be mediated by the immune system [ 7 ]. Research has shown that emotional stress can modulate the immune system through the neural and endocrine systems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress is defined as a state of disharmony in body homeostasis, counteracted by an intricate repertoire of physiologic and behavioral responses that aim to maintain and re-establish the threatened homeostasis (adaptive stress response) [ 6 ]. Psychological stress triggers the neuro-endocrine system, resulting in the continued release of pro-inflammatory mediators and an alteration in normal microbiota, thereby leading to periodontal inflammation [ 7 , 8 , 9 ]. The effect of different aspects of psychological stress, including emotional stress, work-related stress, and dissatisfaction at home or in society, is associated with compromised oral health as suggested by previous studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological responses to stress may alter blood and salivary flow and decrease the immune response to oral pathogens. 24 It is believed that emotional status has serious impact on personal oral health, because selfcare attitude is strongly influenced by the psychological profile. 25,26 According to other researchers, the oral hygiene status can be affected by behavior factors, linked to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease severity depends on several risk factors that are both modifiable and non-modifiable. Non modifiable factors consist mainly in age and genetic susceptibility [ 10 ], whereas modifiable ones include poor oral hygiene [ 11 ], stress [ 12 ], and diseases like diabetes [ 13 , 14 ], although the most recognizable risk factor today is tobacco use [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%